Предмет: Математика,
автор: JessikaMeow
Помогите решить пожалуйста (2x - 4x) - (6x + 6)
Ответы
Автор ответа:
2
Ответ:
x= -0.75
Пошаговое объяснение:
(2x - 4x) - (6x + 6)=0
2x-4x-6x-6=0
-8x=6
x= -0.75
JessikaMeow:
Спасибо большое!
Автор ответа:
1
Ответ:
-8х-6
Пошаговое объяснение:
(2х-4х)-(6х+6)
2х-4х-6х-6
-8х-6
Тут нету уравнения. И получается нужно подобные провести и т.д.
Похожие вопросы
Предмет: Русский язык,
автор: kenzhebay
Предмет: Русский язык,
автор: alexnikiforoff
Предмет: Русский язык,
автор: daniyar02
Предмет: Биология,
автор: Baatullai
Предмет: Литература,
автор: Jkoll